Financial Constraints, Firm Characteristics and Exports: Evidence from Turkish Manufacturing Firms - Burgac Cil, Almila; Dulger, Fikret (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to examine the relationship among firm exports and financial constraints and the other firm characteristics as total factor productivity (TFP), foreign demand growth, market concentration and mark-up using firm-level data of Turkish manufacturing sector for the period of 2003-2013 in terms of the heterogeneous firm trade models as the analysis unite for international trade models that have led to a comprehensive change in international trade theories since the1990s. According to the results, the TFP affect positive on export of firms while financial constraints restrict firms’ export activity. During the analyzed period, foreign demand growth, as expected, increase firms’ exports while reducing market concentration. These findings of the study are important for contributing to the use of policy makers by producing healthy and reliable knowledge in the formulation of international trade and industrial policies with emphasizing impact of the firm characteristics on exports. Keywords: Heterogeneous Firms, Firm Characteristics, Turkish Manufacturing Industry JEL Classifications: F10, F14, L25